Soft power as a policy rationale for international education in the UK: A critical analysis - Lomer, Sylvie (Higher education, 2017)
This article presents the results of a textual analysis conducted on policy discourses on international students in the UK between 1999 and 2013. A number of rationales for and against increasing their numbers have been made, which have largely remained consistent over changing political administrations. One key rationale is that international students enhance the UK's global political influence through its soft power. Critical analysis indicates that a number of unsubstantiated assumptions are made, representing international higher education and students in an outdated power relation predicated on Cold War politics. Key assumptions are that international students change their political attitudes and identify with the host country as a result of positive experiences. Later they are supposed to return home and reach positions of influence, which they exert in favour of the UK. They are represented to feel the same whether on scholarship or self-funded; and behave in predictable, similar ways. These representations of students as social subjects have disciplinary implications, which should be a topic for critical debate and potentially resistance in pedagogical contexts. (HRK / Abstract übernommen).